The Weak Galerkin Method for Linear Hyperbolic Equation (Communications in Computational Physics, 2018)
The linear hyperbolic equation is of great interest in many branches of physicsand industry. In this paper, we use the weak Galerkin method to solve the linear hyperbolicequation. Since the weak Galerkin finite element space consists of discontinuouspolynomials, the discontinuous feature of the equation can be maintained. The optimalerror estimates are proved. Some numerical experiments are provided to verifythe efficiency of the method.
Keywords: Weak Galerkin finite element method; linear hyperbolic equation; error estimate.